2012
DOI: 10.3748/wjg.v18.i26.3389
|View full text |Cite
|
Sign up to set email alerts
|

Osteopontin increases hepatocellular carcinoma cell growth in a CD44 dependant manner

Abstract: This study demonstrates that OPN plays a significant role in the proliferation of HCC through interaction with the cell surface receptor CD44. Modulation of this interaction could represent a novel strategy for the control of HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 34 publications
1
20
0
Order By: Relevance
“…1E), indicating that HCV-infection does not induce the formation of OPN splice variants. In contrast, recent studies have shown the formation of two splice variants of OPN in HCC [48]. This could be due to different cell types and the source of HCC tissue samples used in those studies.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…1E), indicating that HCV-infection does not induce the formation of OPN splice variants. In contrast, recent studies have shown the formation of two splice variants of OPN in HCC [48]. This could be due to different cell types and the source of HCC tissue samples used in those studies.…”
Section: Discussionmentioning
confidence: 81%
“…Full-length OPN is composed of about 314 amino acids and there are also functionally important cleaved products and occasional splice variants [24], [38], [48]. In HCV-infected hepatoma cells, we could observe only full-length OPN mRNA (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…By utilizing more sensitive machines and methods, low abundance proteins that change with cancer development can be found and may be more directly related to the cancer. Using such methods, proteins such as peroxiredoxin 3 (Ai et al, 2006; Chen et al, 2010b; Guo et al, 2007; Li et al, 2008; Lu et al, 2010; Qiao et al, 2012; Song et al, 2009; Wang, 2007; Yue et al, 2007) and osteopontin have been identified as potential markers of HCC (Abu El Makarem et al, 2011; Chen et al, 2010a; Chen et al, 2011; Kim et al, 2006; Lin et al, 2011; Phillips et al, 2012; Qin and Tang, 2004; Shang et al, 2012; Tang et al, 2004; Ye et al, 2003; Zekri et al, 2011). While these markers have been shown to be elevated in other cancers, they may still have great value in the early detection of liver cancer (Chahed et al, 2008; Lehtonen et al, 2004; McAllister et al, 2008; Mirza et al, 2008; Park et al, 2008; Park et al, 2007; Reiniger et al, 2007; Schremmer et al, 2007; Tigrani and Weydert, 2007; Tuck et al, 2007; Whiteaker et al, 2007).…”
Section: Proteomic Identification Of Biomarkers Of Liver Cancermentioning
confidence: 99%
“…Up-regulation of cell proliferation is associated with down-regulation of p27 and p21 and up-regulation of cyclin D1 [81]. Osteopontin plays role in the proliferation of HCC through interaction with the cell surface receptor CD44 [82] and is considered the key mediator for vasculogenic mimicry [83]. Baxinteracting factor is over-expressed in HCC and correlates with shortened survival [84].…”
Section: Hepatocellular Carcinomamentioning
confidence: 99%